FAKTOR – FAKTOR YANG MENDORONG PAKISTAN UNTUK MELAKUKAN KERJASAMA MILITER DENGAN RUSIA PADA TAHUN 2010 – 2014 - Sukma Dewi, Ni Luh Gede Ayunitha; Fasisaka, Idin; Nugraha, A.A Bagus Surya Widya (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 1 (2017), 2017)
The aim of this research is to explain the military cooperation between Pakistan and Russia caused by Indian massive military cooperation with US since 2005. This writing applied a qualitative method with library research and secondary data. This research used cooperation under security dilemma concept to overview the military cooperation between Pakistan and Russia in 2010 caused by Pakistan face threat with India who do the military cooperation with US and used balance of power concept to overview the development of Pakistan military capability in balance of Indian military capability. The result of this research is to extend the military cooperation between Pakistan and Russia in 2010 because Pakistan face threat from Indian military and US in 2005. The point of this research is the increasion of military power will make the other states face threat and will increase military power to balance the state; therefore, it called balance of power. Keywords : Security Dilemma, Military Cooperation, Balance of power.